The Implementation of Aceh Qanun on Halal Labeling for MSMEs in West Aceh Regency - Nila Trisna; Putri Kemalasari; Rachmatika Lestari; Adella, Adella Yuana; Yayuk Eko Wahyuningsih (JUSTISI, 2024)
The purpose of this study is to determine the implementation of Aceh Qanun Number 8 of 2016 on the Halal Product Assurance System (The Aceh Qanun on Halal Label) on Micro, Small, and Medium Enterprises (MSMEs) and to understand the supervision of the implementation of the Aceh Qanun on Halal Label in West Aceh Regency. The study method used is empirical juridical, producing descriptive data regarding implementing the Aceh Qanun on Halal Label towards MSMEs in the West Aceh Regency. This study is important because data from the Health Office of West Aceh Regency shows that 30 MSMEs have obtained halal certificates. In comparison, 64 MSMEs do not have halal certificates for their marketed food products. Based on the data, this fact does not comply with the provisions of Article 4 of Law Number 33 of 2014 on Halal Product Assurance (hereinafter referred to as the Halal Product Guarantee Law 2014), which obliges all products traded in Indonesia to have halal certification. This provision is in line with Article 4 of the Aceh Qanun on Halal Label, which states that the Halal Product Assurance System aims to provide protection, peace of mind, and legal certainty to the community in consuming and using Halal and hygienic products for physical and spiritual health. The assurance of halal products refers to legal certainty regarding the halal status of products, proven by halal certificates, halal registration numbers, and halal labels. Many MSMEs in West Aceh do not have halal product certificates, so the objectives of the Aceh Qanun on Halal Label have yet to be well implemented. The suboptimal supervision also influences the suboptimal implementation of the Aceh Qanun on Halal Label. This supervision involves various West Aceh Regency Local Government institutions, such as the Ministry of Religious Affairs and the Health Office. The main constraint is the limited funds allocated for such supervision, resulting in suboptimal halal product supervision for MSMEs in West Aceh.